2017
DOI: 10.1080/08830185.2017.1380200
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors: Significance, ligands, signaling pathways, and functions in mammals

Abstract: This review attempts to cover the implication of the toll-like receptors (TLRs) in controlling immune functions with emphasis on their significance, function, regulation and expression patterns. The tripartite TLRs are type I integral transmembrane receptors that are involved in recognition and conveying of pathogens to the immune system. These paralogs are located on cell surfaces or within endosomes. The TLRs are found to be functionally involved in the recognition of self and non-self-antigens, maturation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
259
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(275 citation statements)
references
References 119 publications
0
259
0
6
Order By: Relevance
“…DNAs and RNAs) [79]. However, it is beyond the scope of the present article to discuss the detail of each TLR signaling pathway that is described elsewhere [80][81][82][83][84][85]. Table 1 is summarizing the numbers of TLRs found in mammalian species mainly in humans and laboratory mouse and their role in pathogen recognition, TLR SNPs and disease association and expression pattern.…”
Section: Current Scenario In Tlr Biology Regulation Of Innate Immunementioning
confidence: 99%
“…DNAs and RNAs) [79]. However, it is beyond the scope of the present article to discuss the detail of each TLR signaling pathway that is described elsewhere [80][81][82][83][84][85]. Table 1 is summarizing the numbers of TLRs found in mammalian species mainly in humans and laboratory mouse and their role in pathogen recognition, TLR SNPs and disease association and expression pattern.…”
Section: Current Scenario In Tlr Biology Regulation Of Innate Immunementioning
confidence: 99%
“…Alternatively, it also activates NF-κB by interacting with receptor-interacting protein-1. TRIF further interacts with TRAF3 and the phosphatidylinositol 3-kinase (PI3K)-AKT pathway resulting in the nuclear translocation of interferon regulatory factor 3 (IRF3) and IRF2, respectively (Brown, Wang, Hajishengallis, & Martin, 2011;Ostuni, Zanoni, & Granucci, 2010;Patel et al, 2012;Vidya et al, 2018).…”
mentioning
confidence: 99%
“…Our results indicated that the macrophage activation induced by rFIP-glu involved Toll-like receptors and MAPKs signaling pathways in macrophage RAW264.7 cells, which is consistent with that PI3K/Akt, the downstream of Toll-like receptor, and MAPK are involved in the activation of macrophages (34, 8789). TLR4 is critical in immune responses and involved mainly in inflammation responses (90). TLR4 can be recognized and activated by many stimuli such as polysaccharides, and its expression increases, and then activates PI3K/Akt and MAPKs pathways, with introduction of a pool of inflammatory mediators (30, 34, 43, 87, 91).…”
Section: Discussionmentioning
confidence: 99%